The English Register in Social Media Instagram - Maharani, Sang Ayu Isnu; Tri Ediwan, Tri Ediwan (Humanis; Vol 27 No 3 (2023), 2023)
This research entitled "English Register in Instagram Social Media". This research is conducted with the aim at identifying and mapping the use of English registers in social media Instagram and specifically is to find out the function of the usage of those registers. This research is a-qualitative descriptive research. The method applied for this research is observation method with note-taking and screen shot technique. To answer the formulated problems, this research applied register theory from Halliday (1994).